Making an Edition in an App - Barbara Bordalejo; Lina Gibbings; Peter Robinson; RIchard North (Digital Medievalist, 2021)
The massive increase in the use of mobile devices over the last years, with over half of all accesses to the internet now coming from mobile devices, presents a challenge and an opportunity to textual scholars. It has long been suggested that digital technologies may help scholarly editors find new audiences for their work: work which has traditionally lain on library shelves with only the occasional visitor. In this paper we describe an attempt to plan, make and distribute an edition -- the CantApp, presenting in its first iteration the General Prologue of Geoffrey Chaucer’s Canterbury Tales -- designed specifically for mobile device use (Chaucer 2020). We reflect on the difficulties we faced, the initial reception of the app, and draw conclusions which might be useful for other scholarly projects.